The Study of Human Physiological Aspect; The Implementation of Clean Production Technology Through Participatory Ergonomic Decreases Workers’ Musculoskeletal Disorders - Wahyu Susihono; I Putu Gede Adiatmika (Journal of Global Pharma Technology, 2018)
Metal manufacturing industries in Bali are spread in Klungkung Regency, Bali. The position of the metal manufacturing industries is in buffer sector of Bali tourism development, so that the stability of sales and production in each period continues to increase. Demand for product quality assurance is carrying out by exporters, including guaranteeing environmentally friendly process. There are many high-quality products are rejected in international market due to the fact that metal manufacturing industries have not consideredhuman and environmental factors (eco-labeling) in their production activity. Companies are switched from Industrial Systems Type I to Closed Loop Industrial System. Various environmental management and industrial management approaches have been carried out, but the current literature review has not reached human physiological aspect. This research is experimental research using treatment by subject design. The result shows that the implementation of clean production technology through participatory ergonomic is able toincrease work performance, in the form of the decrease of musculoskeletal disorders as much as 34.66%.Keywords: Physiological, Musculoskeletal disorders, Metal industry.